Narrative Ecosystem for Edutainment: Ethical Mindset Application in Children's Series and YouTube - Urbano , Rosalía (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The children's series and videos on social media are recognized as significant educommunicators. The study aims to identify values, positive educational contributions, and pedagogical questions within the first season and songs of the children's brand C&C. An interpretative investigation was conducted using qualitative methodology to develop grounded theory. Data were analyzed and interpreted through unstructured and semi-structured interviews, document review, and participant observation. Validation was achieved through triangulation, and theoretical coding was carried out in Atlas.ti. Results reveal values like solidarity, learning from mistakes, and teamwork, while also highlighting issues with unclear explanations and games unsuitable for preschool audiences.